Modeling of anisotropic thermal conductivity of polymer composites containing aligned boron nitride platelets: Effect of processing methods. Issue 12 (18th November 2015) - Chen, Lin; Xu, Hong‐Fei; Sun, Ying‐Ying; Du, Xiao‐Ze; He, Shao‐Jian; Lin, Jun; Nazarenko, Sergei
Abstract : Hexagonal boron nitride (h‐BN) can remarkably enhance the thermal conductivity (TC) of polymer composites, while maintaining high electrical insulation. In this article, the previously developed analytical model, which can simultaneously solve the anisotropic TC of polymer composites containing aligned h‐BN platelets, was improved by introducing a power function to define the polymer thickness ratio in the unit cell. The modified model was validated by an excellent agreement with the experimental results from three independent literatures, in which the samples were prepared by either casting (including tape casting and spin casting) or injection molding. The influence of key parameters on the composite TCs was analyzed. It was found that the power n closely relates to the possessing methods for the polymer composites, which are also well correlated with the behavior of anisotropic TC. POLYM. COMPOS., 38:2670–2678, 2017. © 2015 Society of Plastics Engineers